1978
DOI: 10.1038/bjc.1978.144
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of glucose metabolism in carcinoma of the cervix and endometrium of the human uterus

Abstract: Summary.-Twelve enzymes related to the direct oxidative and glycolytic pathways of glucose metabolism were assayed in 88 cancers of the cervix and 48 cancers of the endometrium of the human uterus, and the activities compared with those obtained from a group of control tissues. Significant increases for all but one of the enzymes studied (a-glycerolphosphate dehydrogenase) were found in cancer of the cervix, when compared with normal cervix epithelium. Hexokinase, phosphofructokinase, and aldolase appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…By contrast, a study in a group of cervical and endometrial cancers on the possible association between glycolytic enzymes and tumour grading did not find any correlation between hexokinase activity and degree of malignancy [6]. In a recent study by our group [7], FDG uptake in primary breast cancer was shown to be associated with tumour grade and p53 status.…”
Section: Introductionmentioning
confidence: 61%
“…By contrast, a study in a group of cervical and endometrial cancers on the possible association between glycolytic enzymes and tumour grading did not find any correlation between hexokinase activity and degree of malignancy [6]. In a recent study by our group [7], FDG uptake in primary breast cancer was shown to be associated with tumour grade and p53 status.…”
Section: Introductionmentioning
confidence: 61%
“…For every enzyme, the mean value in the post-radiation samples was less than that in the preradiation tissues. All enzymes studied, with the exception of aGPD, were higher in the pre-radiation cancer samples than in normal cervical epithelium (Marshall et al, 1978a). The reduced activities in the post-radiation samples brought the mean values closer to those of normal cervical epithelium, although most were still significantly higher; exceptions were HK and PGM, where the means were not significantly different, and PFK, where the mean activity in the post-radiation samples was actually less than in the normal cervical epithelium (P<0 O1).…”
mentioning
confidence: 83%
“…Table I presents the radiation dose to the tissues after the first 137Cs implantation. Table II summarizes the enzyme data from all cancer patients, and normal values from our previous paper (Marshall et al, 1978a). In cancer of the cervix, significant reduction in the specific activiAccepted 28 September 1978 ties of the following enzymes occurred in the post-radiation samples: PFK, Ald, En, and LDH (all P<0001), and PGM, and G6PD (P < 0.05).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Also, 18 FDG PET appears particularly appropriate for the detection of distant tumour sites through the entire body [13,14,32,36]. Interestingly, cervical cancers exhibit high rates of GLUT-1 (type-1 glucose transporter) and glycolytic enzymes (type-2 hexokinase, phosphofructokinase and pyruvate kinase), which makes the imaging by means of the glucose analogue theoretically and practically valid for such gynaecological malignancies [37,38,39,40,41]. In addition, metabolic imaging offers the possibility of non-invasive whole-body scanning in a single session, whereas the FIGO staging system recommends a number of radiological and endoscopic studies, iterative explorations that are not only invasive and expensive, but often clinically fruitless [2,3,4,5].…”
Section: Stagingmentioning
confidence: 99%